MUSIC PRESPEKTIF IMAM AL-GHAZALI DAN URGENSINYA DALAM MENGURANGI TINGKAT STRES AKADEMIK MAHASISWA - Muhibbin, Muhibbin; Muzdalifah, Fithri (LPPM Institut Pendidikan Nusantara Global, 2023)
Relita in the field, many students sometimes cannot control the academic anxiety that is being felt, resulting in disharmony in the body and causing stress. This paper belongs to the type of library research, using a literary approach in the form of scientific journals, books, documents, notes, and so on with the aim of generating ideas. Data was collected by reading a number of references from journals, books, and previous results. As for the results of this study that: Music has many benefits, especially for mental health, According to Al Gazali there are 4 levels in listening to music including: lowest level, second level, third level up to the (highest) level While in reducing student academic stress levels there are several reasons which allows music to be used such as: demands that students feel are too heavy which they consider unable to live up to so that the emotions within students become chaotic.